Anatomical variations of renal arteries in adult cadavers in Andhra Pradesh: A multicentric cross-sectional cadaveric study. - Dr. Pratyusha Challa; Dr. Ranzeetha D; Dr. Venkata Pavana Kumari Komarolu; Dr. Lakkireddy Vasanthi (Student's Journal of Health Research Africa)
Background Anatomical variations in renal artery morphology hold crucial significance in surgical, urological, and radiological procedures. Comprehensive knowledge of these variations enhances the success of renal transplantation, angiography, and retroperitoneal surgeries.